BORROWING AS A LANGUAGE PROCESS - Shatov Ivan Alexandrovich (Journals Park Publishing, 2024)
This article examines the processes of borrowing as a language combination. Territorial dialects, together with their own word creation, can enrich themselves by borrowing from other forms of existence of their national language (literary standard, other territorial dialects, from different types of social dialects), non-literary vernacular, etc., as well as from other national languages, including their literary and non-literary forms.
Keywords: concept, borrowing, languages, jargon, argot, system.